Prioritizing Bridges for Seismic Resilience Enhancement: A Case Study of Algeria - mohammed abdellaoui; Mohamed Badaoui; Mahmoud Bensaibi; Said Koriga (The Journal of Engineering and Exact Sciences)
Algeria is located in an active seismic zone, making its bridges vulnerable to damage, especially older ones. Due to the importance of bridges in terms of safety, social, and economic factors, competent authorities must prepare for disasters, particularly earthquakes, by enhancing bridge resilience. However, due to the large number of bridges and lack of funding, it is not feasible to improve all bridges at once. This article proposes a model to determine priorities for enhancing bridge resilience to earthquakes based on expert opinions in three main steps. Step 1: Identification of key criteria, where design phase, bridge health, seismic zone, bridge importance, availability of alternative roads, and disaster insurance are defined as key criteria. Step 2: Calculation of criteria weights using the analytic hierarchy process (AHP) and integration of expert opinions using the Euclidean distance-based aggregation method (EDBAM). Step 3: Calculation of the priority index after evaluating criteria categories. The model was applied to six bridges, and their ranking was established based on the priority index. The model has proven its accuracy and ability to assist decision-makers in identifying priority bridges.